Estimating the Size of the Shadow Economy: Methods, Problems and Open Questions - Friedrich Schneider; Andreas Buehn (Institute for the Study of Labor (IZA), 2016)
This paper presents various methods for estimating the size of the shadow economy and analyzes their strengths and weaknesses. The purpose of the paper is twofold. Firstly, it demonstrates that no ideal method exists to estimate the size and development of the shadow economy. Because of its flexibility, the MIMIC method used to get macro-estimates of the size of the shadow economy is discussed in greater detail. Secondly, the paper focuses on the definition and causal factors of the shadow economy and provides a comparison of the size of the shadow economy using different estimation methods.
Keywords: D78; E26; H2; H11; H26; K42; O5; O17; 330; MIMIC approach; methods to estimate the shadow economy; advantages and disadvantages of the measurement methods; shadow economy estimates